Parting Comments from the Outgoing Editor - Steven N. Waller Ph.D. (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2024)
This short reflective essay captures several transitional thoughts as Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies transitions the editorship of the journal. The following pages offer an examination of the strengths/assets of the journal as well as a “snapshot” of some of the challenges the journal has faced in the last five years. There are several recommendations offered to continue moving the journal forward. Implementation of these suggestions are contingent upon the incoming editor’s and Board of Directors review and approval. Most important need is to think strategically about the sustainability of the journal. This will call for creating to audiences, new opportunities to publish for the membership and including writing for publication as a part of our mentoring efforts.
Keywords: journal; scholarship; membership engagement; sustainability